Feedback of the faculty participants on training workshop on developing multiple choice questions - Piryani, Rano Mal; Piryani, Sunee; Zeba, Nudrat (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Multiple choice questions are commonly used tools for the written assessment of undergraduate health professions students. Faculty members need training for the development of valid and reliable multiple choice questions. For this purpose, Bilwal medical college organized one-day training workshop on developing multiple choice questions for newly recruited faculty members in March 2021. The main objective of the study was to assess the feedback of the participants on training workshop. Methods: This descriptive cross-sectional study assessed the feedback of the participants of training workshop on developing multiple choice questions. The feedback questionnaire had four questions. First was on “rating training workshop on scale 1 to 10 (1=poor, 10=excellent) for usefulness, content, relevance, facilitation and overall”. Second was on confidence of the participants in developing MCQs after participation based on Likert scale 1 to 4 (1=not confident to 4=extremely confident). Third was on perceptions of the participants on strengths of training workshop. Lastly, fourth was on areas for improvement. The data was analyzed for central tendency using microsoft excel. Results: Participants’ feedback rating about usefulness (8.82±1.51), content (8.12±1.69), relevance (8.35±1.46), facilitation (8.41±1.46) and overall (global) rating (8.35±1.41) was remarkable. Their confidence level after participation (3.41±0.51) was noticeable. Conclusions: The perceptions of the participants immediate after the training workshop i.e, their reaction was positive.